1993
DOI: 10.1111/j.1432-1033.1993.tb17602.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiac fatty‐acid‐binding protein from human placenta

Abstract: When a 105000Xg supernatant of human placenta was incubated with [l-I4C]oleate and subjected to Sephadex G-75 gel filtration and HPLC, two fatty-acid-binding protein (FABP) peaks were obtained. One of these, when further purified by carboxymethyl-cellulose, gave one 15.3-kDa FABP with pZ5.3. The other, when chromatographed on DEAE cellulose, separated into two 14.2-M)a FABP with pZ 6.9 and 5.4. Purity of the proteins was checked by SDS/PAGE. Molecular mass, pZ, immunochemical properties and amino acid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…In human placenta, two types of fattyacid-binding proteins (14.2 kDa and 15.3 kDa) were purified and their presence could be related to fetal development [40]. Moreover, in guinea pig, lipoprotein lipase increases by 11-fold during last ten days of gestation and seems to be implicated in fatty acid transfer between mother and fetus [6].…”
Section: Membrane Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In human placenta, two types of fattyacid-binding proteins (14.2 kDa and 15.3 kDa) were purified and their presence could be related to fetal development [40]. Moreover, in guinea pig, lipoprotein lipase increases by 11-fold during last ten days of gestation and seems to be implicated in fatty acid transfer between mother and fetus [6].…”
Section: Membrane Markersmentioning
confidence: 99%
“…However, Thomas et al [6] and Das et al [40] suggested that free fatty acids may be transferred across the placenta in the absence of a concentration gradient due to the action of cytosolic fatty-acid-binding protein in the placenta. In our study, we demonstrated a latency phase in the transport of linoleic acid bound to albumin by brush border membranes suggesting that linoleic acid transport is a complicated process including more than one step.…”
Section: Membrane Markersmentioning
confidence: 99%
“…At least two FABP isoforms have been detected in the syncytial cytoplasm: liver fatty acid binding protein (L-FABP) and cardiac fatty acid binding protein (C-FABP) (25). To become available for the fetus, the fatty acids are thought to cross the basal membrane either through diffusion or with the assistance of FABPs (26).…”
mentioning
confidence: 99%
“…Other authors using self-made antibodies against heart-and liver-type FABP have revealed expression of those proteins in placentas within 5 to 30 weeks of gestation (18). The reason for this discrepancy in our specimens has yet to be elucidated.…”
mentioning
confidence: 58%